Republic of Congo : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waivers of Nonobservance of Performance Criteria, and Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report, 2009)
This paper focuses on the First Review for the Republic of Congo under the Poverty Reduction and Growth Facility (PRGF). Policy implementation under the authorities' PRGF arrangement through 2008 and the early part of 2009 was broadly satisfactory. The quantitative target on the non-oil primary fiscal balance was observed, but the authorities contracted new nonconcessional external debt. The authorities have also made progress in implementing many of the floating completion point triggers under the enhanced Heavily Indebted Poor Countries Initiative.